Pemanfaatan Facebook dalam Pembelajaran Matematika - Oslen Sijabat; Hanter Manik; Maria Manao; Farida Sianturi; Gerhajur Purba; Adi Situmorang; Efron Manik (Universitas Muhammadiyah Enrekang, 2022)
Abstract The emergence of the Covid-19 virus has had a significant impact on learning in schools. Online learning enables teachers to use advances in technology to create innovative mathematics lessons. Seeing that many school children use Facebook in social media is one of the reasons teachers use Facebook as a medium for learning mathematics. The potential of Facebook is used as a medium for learning mathematics because the features in Facebook, such as Facebook live, share, messenger room, notes and quizzes, can create interesting mathematics learning and are liked by students. The use of Facebook as a medium for learning mathematics online, makes students able to learn easily, because students can learn anytime and anywhere, as long as the internet network is connected. Abstrak Kemunculan virus covid-19, membawa dampak yang signifikan pada pembelajaran disekolah. Pembelajaran daring membuat para guru untuk dapat menggunakan kemajuan teknologi dalam menciptakan pembelajaran matematika yang inovatif. Melihat banyak nya anak sekolah yang menggunakan facebook dalam bermedia sosial, menjadi salah satu alasan guru untuk memanfaatkan facebook sebagai media pembelajaran matematika. potensi facebook dimanfaatkan sebagai media pembelajaran matematika karena fitur- fitru dalam facebook seperti : facebook live, share, messenger room, note dan quiz, dapat meciptakan pembelajaran matematika yang menarik dan disukai siswa. Pemanfaatan facebook sebagai media pembelajaran matematika secara online, membuat siswa dapat belajar dengan mudah, karena siswa bisa belajar kapan dan dimana saja, selama jaringan internet terus terhubung.